SYNTHESIS OF MAGNETIC ACTIVATED CARBON (M-AC) WITH LAMPUNG NATURAL MAGNETITE AND BITUMINOUS COAL FROM PT. BUKIT ASAM TBK AS RAW MATERIALS - Prasetyo Marwan, Arief
Indonesia is a country rich in natural resources, one of which is its mineral resources. Magnetite is an example of mineral resources owned by Indonesia, nowdays magnetite can be further processed not only as raw material for the steel industry. Magnetite can be further processed with the addition of activated carbon to produce magnetic activated carbon. Magnetic activated carbon has adsorption properties belonging to activated carbon and also has magnetic properties which are sourced from magnetite magnetism. Because of these two properties magnetic activated carbon is widely used for various purposes ranging from health to the environment. In this study the magnetite used came from Lampung and the coal used was of the type bituminous from PT. Bukit Asam Tbk. A series of magnetic activated carbon synthesis experiments have been carried out, using various variables to study several things, such as: the effect of adding magnetite before and after the activation process to the yield obtained, the effect of the high activation temperature on the yield and surface conditions of the activated magnetic activated carbon, the effect of the length of time activation of the yield and formation of the Fe3C compound. Experimental samples were analyzed using X-ray Diffraction (XRD), Particle Size Analyzer (PSA), Fourier Transform Infrared Spectroscopy (FTIR Scanning Electron Microscope (SEM) and Energy Dispersive X-ray (EDS Mapping). The experimental results show that the addition of magnetite before the activation process of carbon can bind the element of carbon to magnetite, conversely the addition of magnetite after the activation process is not successful. The highest yield is obtained at the variable activation temperature of 850°C and the activation time is 30 minutes. The appearance of the surface of magnetic activated carbon shows the spread of magnetite around the pores of activated carbon, while the Fe3C phase has begun to emerge since using the lowest value variable that is temperature 700°C and the activation time is 30 minutes.